2018
DOI: 10.1002/cctc.201800915
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of One Dimensional MnO2‐TiO2 Nano‐Heterostructures for Enhanced Hole Mediated Oxidation of As(III) in Potable Water

Abstract: The conversion of the toxic As(III) from drinking water is a challenging task and it becomes more difficult when As(III) is present in low concentrations (50-200 ppb). Considering this, the present article demonstrates an easy and cost effective wet chemical synthesis of MnO 2 ÀTiO 2 nanoheterostructures (NHs) and its application as the electrode for the oxidation and subsequent conversion of the comparatively low concentration of As(III) from drinking water. The MnO 2 ÀTiO 2 NHs have been employed as the anod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Where, n=0 to 3 for As(III) and 0 to 4 for As(V). Alongside, another possible route for the oxidation of As(III) to As(V) could be its interaction with the reactive hydroxyl group as given below: trueh++normalOnormalH-normalHnormalO4pt2normalHnormalO+HnnormalAnormals()IIIO3-()3-nnormalHnnormalAnormals()VO4-()4-n+2normalOnormalH- …”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Where, n=0 to 3 for As(III) and 0 to 4 for As(V). Alongside, another possible route for the oxidation of As(III) to As(V) could be its interaction with the reactive hydroxyl group as given below: trueh++normalOnormalH-normalHnormalO4pt2normalHnormalO+HnnormalAnormals()IIIO3-()3-nnormalHnnormalAnormals()VO4-()4-n+2normalOnormalH- …”
Section: Resultsmentioning
confidence: 80%
“…This also indicates that the anchoring of f‐MWCNTs on the surface of anodized SS foil enhances the charge transfer process of the electrode compared to the bare anodized SS foil. The linearity of the LSV plots in both cases, probably indicates that no pinning of Fermi level occurs in the semiconducting materials used within the range of applied voltage . The Nyquist plots of the as‐prepared electrodes (Figure (b)) obtained by performing electrochemical impedance spectroscopy (EIS) study shows that the equivalent series resistance ( R s ) of the pristine anodized SS foil and f‐MWCNTs/anodized SS foil is 6.96 and 5.5 ohm.cm 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the TiO 2 nanotube arrays can provide a stable framework and large surface area to support MnO 2 , and the Ti substrate with a high conductivity can facilitate the electron transfer, further promoting the electrochemical oxidation efficiency. Recently, Sarkar et al used MnO 2 to fabricate one dimensional MnO 2 –TiO 2 nano-heterostructures and demonstrated a good effectiveness of 76% in the electrocatalytic oxidation of As­(III) at a concentration of 200 ppb, which illustrated the great potential of TiO 2 –MnO 2 nano-heterostructures in boosting the oxidation and conversion As­(III) to As­(V) at relatively low concentration . The hetero-interface of MnO 2 –TiO 2 will strengthen the migration/transportation of the charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sarkar et al used MnO 2 to fabricate one dimensional MnO 2 −TiO 2 nanoheterostructures and demonstrated a good effectiveness of 76% in the electrocatalytic oxidation of As(III) at a concentration of 200 ppb, which illustrated the great potential of TiO 2 −MnO 2 nano-heterostructures in boosting the oxidation and conversion As(III) to As(V) at relatively low concentration. 32 The hetero-interface of MnO 2 −TiO 2 will strengthen the migration/transportation of the charge carriers. However, this study as yet has only focused on the electrocatalytic oxidation effect of MnO 2 −TiO 2 nanostructures on comparatively low-concentration As(III), while there are still knowledge gaps regarding the effect of the morphology and preparation conditions of MnO 2 −TiO 2 nanostructures on electrocatalytic oxidation performance.…”
Section: Introductionmentioning
confidence: 99%